IMPLEMENTASI PASAL 36 PERATURAN PEMERINTAH NOMOR 36 TAHUN 2021 TENTANG PENGUPAHAN TERHADAP PEKERJA USAHA MIKRO KECIL DAN MENENGAH DI KECAMATAN TUAH MADANI KOTA PEKANBARU - Farhan, M; Firdaus, Emilda; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Micro, Small, and Medium Enterprises (UMKM) are business units thathave independent productive activities, and can be run by individuals or businessentities, which operate in various economic sectors. operate in various economicsectors. Speaking of labor issues, wage issues remain a major concern inIndonesia as a developing country. The law regarding minimum wage regulationis Government Regulation Number 36 of 2021 concerning Wages. Article 6paragraph (1) of this regulation explains that the policy on minimum wage aimsto ensure that workers/laborers receive sufficient income to meet their livingneeds. Further details regarding this arrangement can be found in Chapter VI ofGovernment Regulation No. 36 of 2021 Article 36 on the Lowest Wage in Microand Small Enterprises which states that the wage is at least 50% of the averagecommunity consumption at the provincial level. However, there are still UMKMworkers who receive wages below the regulated standard.This research is a sociological legal research, namely research thatlooks at the relationship between law and society with the gap between the lawthat should and the law that actually occurs. The research was conducted at theManpower Office of Pekanbaru City and at the Manpower and TransmigrationOffice of Riau Province. This research also contains questionnaires distributed toworkers and employers in Pekanbaru City. Data collection techniques throughinterviews, questionnaires and literature review.From the results of the research that has been conducted, theimplementation has not been maximized. This is because the relevant agenciesmove only based on reports or complaints that are obtained. Factors that causeless than optimal implementation are the lack of human resources or members toinspect throughout Riau Province and the lack of facilities and infrastructureobtained from the government. Efforts made by related agencies if they get areport, namely by providing guidance, supervision and action to the reportedparty.Keyword : Wage, Labor, UMKM.